Polypharmacy and suicide attempts in bipolar disorder - Gazalle,Fernando Kratz (2007)
OBJECTIVE: The aim of this study was to assess the association between suicide attempts and the use of multiple drugs in patients with bipolar disorder. METHOD: One hundred sixty-nine bipolar disorder outpatients diagnosed using the DSM-IV Structured Clinical Interview were included. Demographic and socioeconomic data, number of medications currently in use, history of suicide attempts, number of years undiagnosed, age of onset and current psychiatric co-morbidities were assessed using a structured questionnaire and DSM-IV criteria. The main outcome measure was the number of psychotropic drugs currently in use. RESULTS: Approximately half of all patients (48.5%) presented a history of suicide attempt; 84% were using more than one medication, and 19% were using more than three drugs. The most frequent combinations of drugs used by these patients were: lithium + valproate (17%); lithium + antipsychotics (10%); lithium + valproate + antipsychotics (9%); and antidepressants + any drug (6%). The number of suicide attempts was associated with the use of multiple drugs. CONCLUSIONS: Our findings support the notion that the use of combination therapy in bipolar disorder may be related to severity of the BD, such as number of suicide attempts.